Pengerasan Permukaan Baja Perkakas HSS M41 dengan Teknik Pelapisan Metal Spray - Tarigan P; L Juwita (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2002)
Intermetallic compound Fe-AL has good strength and hardness properties. Those properties were required Io improve the wear resistance of component which its application always contact with another part like cutting tool in machining processes. This experiment was carried out to improve the wear resistance of metal, which in this case is high-speed steel (HSS M41). This preliminary experiment was focused on to form the Intermetallic compound Fe-Al layer in the surface Of the steel, This layer was obtained by metal spray technique in which Al-Si spray to the surface of base metal HSS M41 and then heat-treated at 850oC, The holding time of heat treatment for 4 hours, 6 hours and 8 hours respectively was used, Experimental results showed holding time of heat treatment process was influenced to forming the intermetallic layer, thickness and hardness was specimen with heat-treated at 850 OC and holding time 8 hours exhibit the maximum hardness of 1120 HV and also increase the lifetime from 1.84 days to 14.125 days. The thickness of intermetallic layer was 0.81 mm.